Open skies for Africa, a principled approach to the implementation of the Single African Air Transport Market (SAATM) - Sammy, William Kiema (Department of Private Law, 2025)
The Establishment of an African Single Aviation Market (SAM) is a difficult and evolutionary process, particularly considering the continent's socio-political context and the inherent challenges of integrating a continent as expansive and diverse as Africa. The most significant effort to reform the African aviation industry started with the Yamoussoukro Decision in 1998), which instituted minimum rules for establishing the African SAM. However, the continental implementation of the YD has proved to be Sisyphean. Whereas other regions such as the European Union (EU) and the Association of South East Asian Nations (ASEAN) have successfully established SAMs through evolutionary processes shaped by each of these regions' unique set of values, identities, and circumstances, the realisation of the African SAM has lulled due to the lack of an approach that appreciates the unique African circumstances as characterised by its vastness and varying national priorities and interests, the continent's aviation history and development, the legal and institutional framework on aviation, and the varying approaches to liberalisation among the continent's Regional Economic Communities (RECs). Similar to other areas, integration and cooperation in the African air transport sector has largely borrowed the EU formalistic, top-down approach and has found itself caught in the straightjacket of supranationalism and a scrupulous timetable of implementation of commitments, without appreciating the flexibilities inherent in Regional Integration Arrangements (RTAs) in Africa. Consequently, the African SAM has failed to replicate the EU success story, leading to further disintegration of the continental efforts into incoherently coordinated sub-regional initiatives, overlap of institutions and paralysis of the Pan-African institutions of the YD. The gravamen of this thesis is to propose a principled approach to implementing SAATM. This approach foregrounds a holistic implementation of the YD, involves all relevant stakeholders and is within the broader context of Agenda 2063 initiatives and other air law treaties. The approach puts premium on supporting aviation policies such as aviation safety and security, sustainable aviation financing, fair competition, and environmental concerns. The holistic implementation of the YD is to be undergirded by the principle of variable geometry, which is a concept in regional integration that allows countries to be flexible and pursue progressive and differentiated speed towards integration, by allowing a sub-group of countries that are willing and ready to advance to greater levels of integration than the whole. The thesis contextualises the principle of variable geometry in the aviation industry and explains how it can be used in the implementation of the YD and the operationalisation of SAATM. The thesis concludes with general recommendations on the critical policy gaps identified in the study.